2008
DOI: 10.1029/2007ja012333
|View full text |Cite
|
Sign up to set email alerts
|

Globally nonsimultaneous Forbush decrease events and their implications

Abstract: [1] Forbush decrease (FD) events are supposed to happen simultaneously over the globe of the Earth. However, there have been several reports on nonsimultaneous FD events. We investigate for the first time the properties of nonsimultaneous FD events and the solar wind conditions causing such events in detail in order to determine what solar wind conditions lead to global simultaneity of FD events. We examined the hourly data of the Oulu Neutron Monitor (NM) station from 1998 to 2002. We have selected 49 FD even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 45 publications
5
78
1
Order By: Relevance
“…The difference in time of maximum decrease between stations represented by the same color code is about 1-3 h while the difference in time of detection between different color codes might be as long as a day. This indicates, as noted by Oh et al (2008), that globally nonsimultaneous Fds could be simultaneous at similar local times. It is believed that the differences in the time of observation could be attributed to changes in the directions of IMF passing over the Earth.…”
Section: Utmentioning
confidence: 80%
See 1 more Smart Citation
“…The difference in time of maximum decrease between stations represented by the same color code is about 1-3 h while the difference in time of detection between different color codes might be as long as a day. This indicates, as noted by Oh et al (2008), that globally nonsimultaneous Fds could be simultaneous at similar local times. It is believed that the differences in the time of observation could be attributed to changes in the directions of IMF passing over the Earth.…”
Section: Utmentioning
confidence: 80%
“…They agreed that the increase before the main phase onset time is dependent on local time. Recently, Oh et al (2008) and Oh and Yi (2009) investigated the global simultaneity of Fds by comparing the main phase of large and small Fds observed by three neutron monitors. Their definition of a simultaneous event was not based on the onset time or the time of maximum decrease in cosmic ray intensity.…”
Section: Introductionmentioning
confidence: 99%
“…When magnetic clouds and IP shocks pass, the cosmic ray intensity decreases, and if the perturbation is strong, a sharp drop in cosmic ray intensity occurs. Oh et al (2008), and Oh & Yi (2009, 2011, classified FDs observed using the NMs located at high latitudes (Inuvik, Magadan, and Oulu) into simultaneous and nonsimultaneous FD events. They explained that the main phase of the cosmic-ray-intensity profile of simultaneous FD events observed at these three NM stations, overlap in universal time (UT), while the main phase of nonsimultaneous FD events overlap in local time (LT).…”
Section: Introductionmentioning
confidence: 99%
“…They can also be detected in muon signals. FD events are caused by magnetic‐field variations linked to the interplanetary shock‐sheath region [ Parker , ; Gosling et al ., ; Hundhausen , ; Kennel et al ., ; Lockwood et al ., ] and the magnetic cloud [ Burlaga et al ., , ; Klein and Burlaga , ; Sanderson et al ., ; Zhang and Burlaga , ; Badruddin , ; Oh et al ., ; Oh , ]. Such events act as interplanetary shock drivers.…”
Section: Introductionmentioning
confidence: 99%